Isotherm and main thermodynamic characteristics of adsorption of carbonyl sulfide molecules on zeolite KA (MSS-558) - Ergashev, Oybek; Bakhronov, Khayot; Asfandiyorov, Marufjon; Kokhkharov, Mirzokhid; Ganiev, Abror; Akhmedova, Nodira; Tulyaganova, Shaxnoza; Nazirov, Kamoliddin; Esonkulova, Nazirahon (Edelweiss Applied Science and Technology, 2025)
This paper presents experimental results of isotherm and basic thermodynamic characteristics of COS molecules on zeolite KA. Differential values of adsorption free energy and entropy were calculated, and a correlation was found between adsorption-energetic characteristics and the crystallochemical structure of the adsorbent. A regular correlation was established between the amount of COS adsorbed on zeolite KA and the corresponding differential heat values. In the initial stage, under the influence of COS molecules, K+ cations in the structure of zeolite KA migrate from the internal matrix to the surface, forming ion-molecular complexes with the COS molecules. It was shown that at an adsorption amount of 0.1 mmol/g, the K+ cations completely migrate to the surface of the zeolite. Based on the BET equation, it was shown that the monolayer adsorption capacity of COS molecules on KA zeolite is 0.01 mmol/g. The average value of the molar integral entropy of COS adsorption on KA zeolite was -13 J/mol·K, which indicates that the mobility of COS molecules in the zeolite is lower than in the liquid phase and is close to that in the solid phase, leading to a strong inhibition of adsorption mobility on the COS cations.